Thai temple area: facilities assessment for emergency shelter use - Doungjai Limsaksri; Yanin Rugwongwan (IOP Conference Series Earth and Environmental Science, 2023)
Abstract An emergency shelter is a place where people live temporarily in case of an emergency. In Thailand, the emergency shelter usually is constructed by amending the temple area or using the temple area itself. Since the purpose of the temple is to be a place for religious activities, the amount of the area may not fit for being an emergency shelter. The purpose of this research are to evaluate the adequacy of the residential area and the supporting rate for the number of people in the community. For the research method, this research uses the temple area surveying in the case study temple. The result found that using the temple area as the emergency shelter is not sufficient when compared to the population in the surrounding communities. In conclusion, using the temple area as an emergency shelter is a policy based on the fact that the temple is a convenient and accessible public space located very close to the community. Normally, these temples are used for religious rituals and monks’ activities, so the physique of the building is mainly to support those types of activities. But when the temple needs to be modified into an emergency shelter, the amount of space are not sufficient to support the people from the communities around the temple and making it more difficult for the victims to live.
Keywords: Evacuation and Crowd Dynamics